STUDY OF UZBEK LANGUAGE FOOD NAMES IN SCIENTIFIC INTERPRETATION - Rushana Nabiyeva Jamal qizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
The article is about the study of new food names in world linguistics and Uzbek linguistics in different aspects, and it is explained on the basis of evidence. Based on the collected materials, it was explained that the names of the new food items under analysis form a specific lexical-thematic group and take a place in the lexical fund of the Uzbek language. Food names are considered a lexical-semantic group in the language system, just as a specific lexeme in the language is a lexical-thematic group in the language system and a further dividing lexical-semantic group, and "food" covers all lexical items that refer to. The acquisition of food names in the language is directly related not only to linguistic activity, but also to the cultural aspect of society. Because there is an influence of language on culture, and culture on language, such interpretations are a source for research in a more sociolinguistic aspect. Because culture is an important value for every nation, it is natural that understanding or changing the names of food has a more subtle significance in expressing their national identity. From this point of view, food names are valuable for any nation as unique cultural realities.